Structure of Optimal Control in Optimal Shaping of the Steel Arch - Mikulski, Leszek; Jasińska, Dorota; Dąbrowska, Olga (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the problem of optimal shaping of the H-bar cross-section of a steel arch that ensures minimal mass. Nineteen combinations of nine basic load states are considered simultaneously in the problem formulation. The optimal shaping task is formulated as a control theory problem within the formal structure of the maximum Pontriagin`s principle.
Keywords: shape optimization; optimal control; arch; multipoint boundary value problem